2019
DOI: 10.3389/fphys.2019.01311
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Responsible for Genetic Hypertension in Schlager BPH/2 Mice

Abstract: It has been 45 years since Gunther Schlager used a cross breeding program in mice to develop inbred strains with high, normal, and low blood pressure (BPH/2, BPN/3, and BPL/1 respectively). Thus, it is timely to gather together the studies that have characterized and explored the mechanisms associated with the hypertension to take stock of exactly what is known and what remains to be determined. Growing evidence supports the notion that the mechanism of hypertension in BPH/2 mice is predominantly neurogenic wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 149 publications
(280 reference statements)
3
23
0
Order By: Relevance
“…Male BPH/2 mice have been utilized to investigate basic cardiometabolic physiology. In adulthood, they are hypertensive with a greater metabolic rate and decreased body weight compared to normotensive BPN/3 males [2], which is similar to what is observed in comparison of BPH/2 and BPN/3 females. Genome Wide Association Studies…”
Section: Plos Onesupporting
confidence: 79%
See 2 more Smart Citations
“…Male BPH/2 mice have been utilized to investigate basic cardiometabolic physiology. In adulthood, they are hypertensive with a greater metabolic rate and decreased body weight compared to normotensive BPN/3 males [2], which is similar to what is observed in comparison of BPH/2 and BPN/3 females. Genome Wide Association Studies…”
Section: Plos Onesupporting
confidence: 79%
“…RAS genes were considered as they are important for cardiovascular adaptations in mammals, including blood pressure regulation, and may contribute to female BPH/5 borderline hypertension before pregnancy. We hypothesized that BPH/5 and BPH/2 mice would possess similar mutations in RAS genes, specifically angiotensinogen (Agt) and kallikrein, as previously described in BPH/2 [2]. BPH/5 female mice have non-synonymous mutations in Agt, but not in angiotensinogen converting enzyme (Ace) and Agt receptor (Agtr) 1a.…”
Section: Plos Onementioning
confidence: 95%
See 1 more Smart Citation
“…However, the mechanism responsible for the antihypertensive effect of RDN is still unclear. An elevated BP coupled to increased sympathetic drive [ 33 , 34 ]. Specifically targeting afferent renal nerves in deoxycorticosterone acetate-salt model [ 32 , 35 , 36 ] or efferent nerves in Dahl salt-sensitive rats [ 37 ] chronically lower BP.…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%
“…There are a number of rat and mouse strains for example that have been bred or genetically manipulated to develop high blood pressure. Strains such as the spontaneously hypertensive rat (SHR) and Schlager BPH mouse developed in the 1960's and 1970's, respectively have been widely used (Okamoto and Aoki, 1963;Schlager, 1974;Jackson et al, 2019). Studies from our laboratory suggested that the BPH mice had a neurogenic form of hypertension involving a much greater contribution of the sympathetic nervous system (SNS) (Davern et al, 2009).…”
Section: Microarray and Gwas Studiesmentioning
confidence: 99%